Antileukemic Effect of Palladium Nanoparticles Mediated by White Tea (Camellia sinensis) Extract In Vitro and in WEHI-3B-Induced Leukemia In Vivo. (19th August 2020) - Othman, Hemn; Rahman, Heshu; Mohan, Syam; Aziz, Sadat; Marif, Hardi; Ford, Dianne; Abdulsamad, Nozlena; Amin, Kawa; Abdullah, Rasedee
Abstract : This study investigated the in vivo antileukemic activity of palladium nanoparticles (Pd@W.tea-NPs) mediated by white tea extract in a murine model. The cell viability effect of Pd@W.tea-NPs, "blank" Pd nanoparticles, and white tea extract alone was determined in murine leukemia WEHI-3B cells and normal mouse fibroblasts (3T3 cells). Apoptotic and cell cycle arrest effects of Pd@W.tea-NPs in WEHI-3B cells were evaluated. The effects of Pd@W.tea-NPs administered orally to leukemic mice at 50 and 100 mg/kg daily over 28 days were evaluated. Pd@W.tea-NPs reduced the viability of WHEI-3B cells with IC50 7.55  μ g/ml at 72 h. Blank Pd nanoparticles and white tea extract alone had smaller effects on WHEI-3B viability and on normal fibroblasts. Pd@W.tea-NPs increased the proportion of Annexin V-positive WHEI-3B cells and induced G2/M cell cycle arrest. Leukemic cells in the spleen were reduced by Pd@W.tea-NPs with an increase in Bax/Bcl-2 and cytochrome-C protein and mRNA levels indicating the activation of the mitochondrial apoptotic pathway. These effects replicated the effects of ATRA and were not observed using blank Pd nanoparticles. Pd@W.tea-NPs afford therapeutic efficacy against leukemia likely to pivot on activation of the mitochondrial pathway of apoptotic signaling and hence appear attractive potential candidates for development as a novel anticancer agent.